A Study on Investment Behavior of Working Women From Middle Class Families (International Journal of Food and Nutritional Sciences, 2022)
Investment is one of the major issues of the middle income families as their small savings of today are meeting the expenses of tomorrow. The person dealing with the planning must know all the various investment choices can be chosen for the purpose of attaining the overall objectives. Women’s investment is necessary to meet the uncertain future emergencies in the family. A number of studies have revealed that women and men have different investment behavior. Women hold low risk tolerance and also earn less return from their investments. The aim of this research was to examine the investment behavior of the working women’s from middle income class families in Palghar. The data has been analyzed using frequency analysis, descriptive statistics, percentage and person correlation coefficient analysis with the help of statistical software.